Schooling Impacts of Conditional Cash Transfers on Young Children: Evidence from Mexico - Behrman, Jere R. (2009)
This paper evaluates impacts of Oportunidades, a Mexican conditional cash transfer program, on educational outcomes 5.5 years after program initiation for a group of children who were age 0 to 8 years pre-program. The oldest children within this age range received educational scholarships. The youngest children did not receive the scholarships because they had not yet started the third grade of school (the initial grade for scholarships), but were beneficiaries of the program’s health components that included nutritional supplements for children 24 months of age or younger. All of these children also may have benefitted more generally from increased household income resulting from the program. This paper investigates how the program differentially affected younger and older children within this age range and examines whether the early nutritional intervention led to improvements in subsequent educational performance. The program impact estimates are derived from a randomly assigned treatment and control group, which participated for different lengths of time in the program, and from a matched comparison group that had not participated prior to the collection of data in 2003. The empirical findings show positive program impacts on reducing ages at entering school for the younger children as well as on accumulated grades of schooling after 5.5 years of benefits for older children, with estimates implying a 1 percent reduction in the age of entry to primary and an increase in grades of schooling completed to date of about 8 to 9 percent.